#### Answer

$49x^6y^2$

#### Work Step by Step

RECALL:
(i) $(a^m)^n=a^{mn}$
(ii) $(ab)^m = a^mb^n$
Use rule (ii) above to obtain:
$=7^2(x^3)^2y^2
\\=49(x^3)^2y^2$
Use rule (i) above to obtain:
$=49x^{3(2)}y^2
\\=49x^6y^2$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$49x^6y^2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.